Answer:
y=-7
Step-by-step explanation:
y-y1=m(x-x1)
y-(-7)=0(x-5)
y+7=0
y=0-7=-7
A. 6082
B.120687
C.1188228
D.19042587
Answer:
15
Step-by-step explanation:
8.25 minus 7.80 is 0.45 45 divided by 3 is 15 so the answer is 15
Answer:
w^8 - 4w^7 + 6w^6 - 4w^5 + w^4 .
Step-by-step explanation:
(w - w^2)^4
= w^4 ( 1 - w)^4
By the binomial theorem:
= w^4( 1 - 4w + 6w^2 - 4w^3 + w^4)
= w^4 - 4w^5 + 6w^6 - 4w^7 + w^8
= w^8 - 4w^7 + 6w^6 - 4w^5 + w^4 ( Standard form).
1. $9500 because 10*950=9500
2. $95 because 950/10=95
( can explain further )